2007
DOI: 10.1097/01.aids.0000299417.69432.65
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the need for antiretroviral treatment and an assessment of a simplified HIV/AIDS case definition in rural Malawi

Abstract: The field checklist was not a suitable tool for individual staging. Criteria for ART eligibility based on clinical staging alone missed two-thirds of those eligible by clinical staging and CD4 cell count.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 14 publications
(11 reference statements)
1
40
0
Order By: Relevance
“…The three other studies enrolled participants from a rural community as part of a demographic and health survey (DHS) [29], an antenatal clinic as part of a PMTCT programme [27] and patients admitted in medical wards and assessed in an outpatient medical assessment unit [33]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three other studies enrolled participants from a rural community as part of a demographic and health survey (DHS) [29], an antenatal clinic as part of a PMTCT programme [27] and patients admitted in medical wards and assessed in an outpatient medical assessment unit [33]. …”
Section: Resultsmentioning
confidence: 99%
“…One study [31] used the Coulter manual method and in three studies [27, 29, 37], the method was not reported. Only two studies [25, 30] reported that external laboratory quality assurance procedures for CD4 counts were followed.…”
Section: Resultsmentioning
confidence: 99%
“…Median baseline CD4 counts at initiation of HAART have been found to be between 100-150 cells/μl in several low income countries [9-15]. In contrast, a population based study from 2007 indicates that 42% of all HIV patients in Malawi had a CD4 cell count under 350 cells/μl, while 22% had under 200 cells/μl [16]. Shifts to an early treatment start strategy will increase the need for HAART, but few people actually receive HAART.…”
Section: Introductionmentioning
confidence: 99%
“…These can be used to extrapolate for planning purposes to larger urban populations [14]. Careful follow up allowed an estimation of survival [15-17].…”
Section: Introductionmentioning
confidence: 99%